SIGN WITH THE IDENTITY OF LOCAL WISDOM COMMUNICATION THROUGH COSTUME FOR THE PERFORMANCE : ROI LAO KHLUY BANG SAI KAI - CHITTHUAM, KODCHAKORN; ASAVASEMACHAI, TANANPACH; PHASURICHANDAENG, KHOMCHAWAT (Journal of Suan Sunandha Arts and Culture, 2022)
Roi Lao Khluy Bang Sai Kai performance is a creative work of dance art that used symbols as a medium thought the communication are formed and defined to represent both the direct and indirect meanings. Roi Lao Khluy Bang Sai Kai, it was found that in the design of each performance element, signs were used to communicate the identity of the local wisdom heritage, especially the costume design for the performance which communicates the history, way of life, and characteristics of the flutes in different parts of the attire, including the use of shirts and pants in light brown color that is similar to the color of ruak wood that is a staple of flute making. The use of cloth with a pattern is comparable to the cloth pattern used in the way of life of Vientiane (Laos people), as well as jewelry that has design is similar to the Champa Lao flower, which is the national flower of Laos. In addition to referring to the history of the ancestors who formed the community, it also implied that they lived happily ever after. Moreover, the 7 traditional flute patterns of the community, comprising Mai Kad Ngao pattern, Dok Pikul pattern, Krachuap pattern, Rodnam pattern, Hokkamen pattern, Talok pattern and Hin pattern, these are also used as an important part in presenting community identity in this performance.